Platelet Factor 4 Attenuates Experimental Acute Liver Injury in Mice - Drescher, Hannah K.; Brandt, Elisa F.; Fischer, Petra; Dreschers, Stephan; Schwendener, Reto A.; Kowalska, M. Anna; Canbay, Ali; Wasmuth, Hermann E.; Weiskirchen, Ralf; Trautwein, Christian; Berres, Marie-Luise; Kroy, Daniela C.; et al. (Frontiers in Physiology, 2019)
Platelet factor 4 (PF4) is a pleiotropic inflammatory chemokine, which has been implicated in various inflammatory disorders including liver fibrosis. However, its role in acute liver diseases has not yet been elucidated. Here we describe an unexpected, anti-inflammatory role of PF4. Serum concentrations of PF4 were measured in patients and mice with acute liver diseases. Acute liver injury in mice was induced either by carbon tetrachloride or by D-galactosamine hydrochloride and lipopolysaccharide. Serum levels of PF4 were decreased in patients and mice with acute liver diseases. PF4-/- mice displayed increased liver damage in both models compared to control which was associated with increased apoptosis of hepatocytes and an enhanced pro-inflammatory response of liver macrophages. In this experimental setting, PF4-/- mice were unable to generate activated Protein C, a protein with anti-inflammatory activities on monocytes/macrophages. In vitro, PF4 limited the activation of liver resident macrophages. Hence, the systemic application of PF4 led to a strong amelioration of experimental liver injury. Along with reduced liver injury, PF4 improved the severity of the pro-inflammatory response of liver macrophages and induced increased levels of activated Protein C. PF4 has a yet unidentified direct anti-inflammatory effect in two models of acute liver injury. Thus, attenuation of acute liver injury by systemic administration of PF4 might offer a novel therapeutic approach for acute liver diseases.